Rancang Bangun Sistem pengaman sepeda motor yang terintegrasi dengan sistem rem hidrolik berbasis Arduino - Pratama, Handy Nur; Abdurrahman, Abdurrahman (Automotive Science and Education Journal, 2021)
The motorcycle security system aims to prevent motorcycles from being stolen. The motorcycle safety system integrated with an Arduino-based hydraulic brake system is a safety system that utilizes a brake system combined with a microcontroller to create a safety system that prevents the motorcycle from moving because the brake system stops the wheels from turning when there is a theft disturbance on the motorcycle. The research method used is research and development methods. The data analysis technique used is the descriptive statistical analysis technique, namely the percentage calculation technique. The results of the feasibility test of the tool by the expert obtained a total score of 87% (very feasible), the conclusion is that the tool can be used properly.